DYNAMICAL ANALYSIS OF SVEIR MODEL IN SPREAD OF THE MONKEYPOX DISEASE WITH TIME DELAY - Isnu Aji Saputro; Glagah Eskacakra Setyowisnu; Noor Sofiyati; Dian Puspita (Universitas Jenderal Soedirman, 2025)
Monkeypox is an infectious disease whose spread is influenced by various epidemiological factors, one of which is the incubation period. This study developed a mathematical model of Monkeypox, SVEIR, by incorporating a time delay in the transition from an exposed individual to an infectious individual, representing the incubation period. Model analysis shows that the system has two equilibrium points: a disease-free state and an endemic state. Based on the simulation results, a threshold value (tau* ) is obtained, which plays a crucial role in disease control. If the incubation period is below the threshold ( tau<tau*), then R0>1 , and the disease will spread endemically. Conversely, if the incubation period exceeds the threshold (tau>tau* ), then R0<1 , and the disease will disappear from the population